Creation of Android-Based Mobile Learning as Educational Material for Sports Physiology Courses to Enhance Learning Outcomes of Physical Education, Health, and Recreation Students at Medan State University - Ihsan, Miftahul; Setyawan, Dicky B; Aufan, Rifqi; Ilham, Zulpikar (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. This study is a development initiative focused on enhancing learning outcomes via mobile learning, specifically targeting the domain of sports science, with an emphasis on sports physiology courses. Materials and methods. The method employed will be a quantitative approach, utilizing the Research & Development (R & D) framework as outlined by Sugiono. This involves product development and testing to assess the effectiveness of the products in meeting the desired objectives. Results. The developed media is a learning application designed to assist students in studying sports physiology courses, whether online or offline. This teaching material includes lecture content organized by topic, instructional videos showcasing various learning methods, quizzes, and additional resources that facilitate both online and offline learning experiences. The expectation is that the application will serve as an alternative for both online and offline learning during the Covid-19 pandemic. The media developed within the application encompasses all lecture materials, presented through video tutorials, videos, various learning formats, quizzes, and additional resources related to the sports physiology course. Conclusion. This concept arose from the necessity to adapt learning methods during the ongoing coronavirus pandemic, despite the absence of face-to-face interaction and direct practice. Consequently, it became essential to create application-based teaching materials for sports physiology courses, enabling instructors responsible for futsal courses to deliver content effectively through both online and offline platforms. This application will significantly enhance accessibility for students, streamlining their ability to obtain all online lecture materials.